Addressing Uncontrolled Symptoms and Communication Gaps in a Patient with Metastatic Cholangiocarcinoma: Lessons from a Palliative Care Case - Huang, Ian (Medicinus, 2025)
Background : Timely integration of palliative care is essential in managing advanced cancer patients, addressing both physical symptoms and psychosocial distress. Delayed communication of prognosis and inadequate symptom control can result in unnecessary suffering for patients and emotional distress for their families. Case Presentation : We report a 49-year-old male with metastatic cholangiocarcinoma, admitted with severe abdominal pain, nausea, and vomiting. He had undergone a Longmire procedure and gastrojejunostomy three weeks prior. Despite surgical intervention, his symptoms remained poorly controlled. Upon assessment, he expressed fear of death, while his wife struggled with the emotional burden of his prognosis, indicating a lack of prior communication regarding his terminal condition. Symptom management included oral morphine for pain and a combination of ondansetron, omeprazole, and haloperidol for nausea and vomiting, leading to improved symptom control. However, his condition deteriorated with pneumonia and respiratory failure, marking the transition to end-of-life care. He passed away peacefully 15 days after admission. Discussion : This case highlights the consequences of delayed prognosis disclosure and inadequate early symptom management. The absence of structured communication contributed to family distress, underscoring the importance of models like SPIKES in breaking bad news. The need for a multidisciplinary palliative care approach, including psychological support and optimized opioid management, was evident. Conclusions : Early palliative care involvement, proactive symptom control, and clear communication of prognosis are crucial in advanced cancer care. Establishing a dedicated palliative care team can improve quality of life, facilitate shared decision-making, and enhance end-of-life experiences for patients and families.